‘One person can’t deliver it’: exploring teachers’ agency and stance in relation to integrating an interdisciplinary subject in UK primary and secondary schools - Bramley, Ryan Josiah; Little, Sabine; Bishop, Julia (Cogent education, 2025)
The benefits of an interdisciplinary childhood education are becoming increasingly well documented. However, UK-based teachers continue to report difficulties and challenges in implementing interdisciplinary learning and teaching opportunities within their respective National Curriculum frameworks. This article reports the findings of a funded international research project involving collaboration with ten UK-based teachers (five primary, five secondary), who were supported to create and evaluate 100 interdisciplinary lessons (10 per teacher). The teacher participants’ questionnaire and interview responses are conceptualised through the lens of Servage’s four teacher professionalism ‘roles’: the teacher as scientist; caregiver; social justice advocate; and learning manager. Drawing on data from evaluative questionnaires and follow-up semi-structured interviews, we present social justice, perceived benefits across school curriculum, and building on learners’ existing interests amongst our teachers’ reported motivations for integrating an interdisciplinary subject within their school curriculum. Our research also found a series of practical and pedagogical challenges for teachers embedding interdisciplinary learning in their classrooms, including a lack of time and resources, a misalignment with each school’s culture and priorities, and difficulties in evidencing multiple subject coverage. We conclude with a series of practical recommendations for fostering an interdisciplinary, values-based approach across K-12 education.